Students' Views on the Use of Teaching Strategy Through Invention in Digital Illustration Course and an Application Study - CANBOLAT, Cihan; YILMAZ, Meliha (Kastamonu Egitim Dergisi, 2021)
Purpose: The aim of the research is to determine the student's views on the use of instructional strategy in digital illustrationcourse through invention and to conduct a practice study. Graphic design courses is limited research on the use of differentteaching strategies in the processing of instruction and the discovery of more math, science in areas such as were used. It isthought that the research is important in this aspect and will contribute to the related literature.Design/Methodology/Approach: In the research, which was carried out with 24 students who took the Digital Illustrationcourse of Kastamonu University Faculty of Fine Arts and Design, Department of Graphics, education was carried out using theteaching strategy through invention. In this study, in which screening research, which is one of the quantitative researchdesigns, was used, the data were collected with a 5-point Likert-type scale and a graded scoring key.Findings: As a result of the research, it was determined that the students were active in the educational environment throughthe invention, and that the information was discovered and learned. As a result of student opinions, it has been concludedthat the instructor guides the students and gives hints to the students during the problems encountered during the designprocess. It was concluded that the teaching strategy through the invention is the method that prepares the students foracquiring new information, the information learned in the lesson is used in different lessons, and it is beneficial for studentsto develop their thinking, problem solving and creativity skills.Highlights: The intensity of the curriculum and the lack of hours made it difficult to implement the teaching strategy. Inaddition, according to the character design evaluation criteria, it was determined that the products designed in the teachingenvironment through invention were sufficient and incomplete.
Keywords: 4. Education